Effect of cement content and water/cement ratio on fresh concrete properties without admixtures - Marar, Khaled Hamed; Eren, Özgür (My University, 2011)
This paper investigates the effects of cement content and water/cement ratio on workable fresh concrete properties with slump changing between 90 to 110 mm, and determines the relations among fresh concrete properties such as slump, compacting factor, VeBe, unit weight and setting times of mortar with temperature history. The experiments were conducted under laboratory conditions on eight different concrete mixtures prepared from ordinary Portland cement (cement contents of 300, 350, 400, 450, 500, 550, 600 and 650 kg/m3) and crushed limestone coarse and fine aggregates. Relations such as (a) VeBe time/unit weight/slump/K-slump/compacting factor/w/c ratio for cement content, (b) K-slump/compacting factor/unit weight/VeBe time for slump, (c) aggregate/cement ratio/unit weight/VeBe time for compacting factor, and (d) penetration resistance for elapsed time were determined. It was observed that increasing the cement content causes increase in the slump, Kslump, compacting factor and fresh concrete unit weight, and reduces VeBe time. Proposed fresh concrete relationships are quite appropriate for concretes without using any mineral or chemical admixtures. © 2011 Academic Journals.
Keywords: Compacting factor; Fresh concrete; Setting time; Slump; Unit weight; VeBe time